The association between adverse pregnancy outcomes and non-viral genital pathogens among women living in sub-Saharan Africa: a systematic review - Gamberini, Carlotta; Juliana, Naomi C. A.; de Brouwer, Lenya; Vogelsang, Dorothea; Al-Nasiry, Salwan; Morré, Servaas A.; Ambrosino, Elena (Frontiers in Reproductive Health, 2023)
Adverse pregnancy outcomes are the main causes of maternal and neonatal morbidity and mortality, including long-term physical and psychological sequelae. These events are common in low- and middle-income countries, particularly in Sub Saharan Africa, despite national efforts. Maternal infections can cause complications at any stage of pregnancy and contribute to adverse outcomes. Among infections, those of the genital tract are a major public health concern worldwide, due to limited availability of prevention, diagnosis and treatment approaches. This applies even to treatable infections and holds true especially in Sub-Saharan Africa. As late as 2017, the region accounted for 40% of all reported treatable non-viral genital pathogens worldwide, many of which have been independently associated with various adverse pregnancy outcomes, and that include Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, Treponema pallidum and Human papilloma virus. Two databases (PubMed and Embase) were examined to identify eligible studies published up to October 2022. This study reviewed findings on the association between infections by treatable non-viral genital pathogens during pregnancy and adverse pregnancy outcomes among women living in Sub-Saharan Africa. Articles’ title and abstract were screened at first using keywords as “sexually transmitted infections”, “non-viral”, “adverse pregnancy outcome”, “Africa”, “sub-Saharan Africa”, “pregnant women”, “pregnancy”, and “pregnancy outcome”.by mean of title and abstract, subsequently Subsequently,, according to the eligibility criteria, potential articles were read in full. Results showed that higher risk of preterm birth is associated with Treponema pallidum, Chlamydia trachomatis and Candida albicans infections. Additionally, rates of stillbirth, neonatal death, low birth weight and intrauterine growth restriction are also associated with Treponema pallidum infection. A better insight on the burden of non-viral genital pathogens and their effect on pregnancy is needed to inform antenatal care guidelines and screening programs, to guide the development of innovative diagnostic tools and other strategies to minimize transmission, and to prevent short- and long-term complications for mothers and children.